Un modèle de piété et de charité : le décor de la chapelle seigneuriale de Lachapelle-sous-Gerberoy (Oise) et son cycle de la vie de saint Eustache - Géraldine Victoir (In Situ)
The chapel located to the north of the church of Lachapelle-sous-Gerberoy (Oise) was adorned around the middle of the 14th century with an exceptionally long cycle of the life of saint Eustace, which comprises a series of images showing the saint and his wife carrying out the Works of Mercy. The scheme also features figures of saints and a monumental Annunciation. An analysis of the images suggests that the structure of the narrative derives from written Lives of Eustace and that the cycle was particularly suited to act as a model of piety and charity for a lay couple.